The effect of corporate social responsibility and ownership structure on firm value in food and beverage companies in south east Asia - Fitria Dhona Anggraini; Erida Herlina (STIE Perbanas Surabaya, 2018)
This study aims to analyze the influence of corporate social responsibility (CSR) and ownership structure towardfirm value. The independent variable thatused in this study are corporate social responsibility (CSR), institutional ownership, managerial ownership and foreign ownership. The dependent variable that used in this study is firm value which measured by Price to Book Value (PBV) ratio. The sample of this study were taken from several food and beverages companies in Shoutheast Asia that registered in www.orbis.bvdinfo.com which published annual report and annual stock data in 2014-2016.A multiple regression analysis with SPSS 22.0 For Windows was used as the technique data analysis. The result of this study explain that corporate social responsibility (CSR), institutional ownership and managerial ownership have influence to firm value, while foreign ownership does not have influence to firm value.